Harnessing Activin A Adjuvanticity to Promote Antibody Responses to BG505 HIV Envelope Trimers - Carnathan, Diane G.; Kaushik, Kirti; Ellebedy, Ali H.; Enemuo, Chiamaka A.; Gebru, Etse H.; Dhadvai, Pallavi; Rasheed, Mohammed Ata Ur; Pauthner, Matthias G.; Ozorowski, Gabriel; Ahmed, Rafi; Burton, Dennis R.; Ward, Andrew B.; et al. (Frontiers in Immunology, 2020)
T follicular helper (TFH) cells are powerful regulators of affinity matured long-lived plasma cells. Eliciting protective, long-lasting antibody responses to achieve persistent immunity is the goal of most successful vaccines. Thus, there is potential in manipulating TFH cell responses. Herein, we describe an HIV vaccine development approach exploiting the cytokine activin A to improve antibody responses against recombinant HIV Envelope (Env) trimers in non-human primates. Administration of activin A improved the magnitude of Env-specific antibodies over time and promoted a significant increase in Env-specific plasma cells in the bone marrow. The boost in antibody responses was associated with reduced frequencies of T follicular regulatory (TFR) cells and increased germinal center T follicular helper (GC-TFH) to TFR cell ratios. Overall, these findings suggest that adjuvants inducing activin A production could potentially be incorporated in future rational design vaccine strategies aimed at improving germinal centers, long-lived plasma cells, and sustained antibody responses.